Factors affecting the adoption of information and communication technology in small and medium enterprises: a perspective from rural Saudi Arabia. Issue 4 (2nd October 2019) - AlBar, Adnan Mustafa; Hoque, Md. Rakibul
ABSTRACT: Small and medium enterprises (SMEs) can play an important role in the national economy of developing countries. The adoption of information and communication technology (ICT) has enabled local SMEs to participate in the international market. However, little research has addressed issues related to SMEs adopting ICTs, especially in rural areas of Middle Eastern developing countries such as Saudi Arabia. Using the extended technology-organization-environment framework with personal innovativeness, this study examined the factors that influence the adoption of ICTs among SMEs in rural areas of Saudi Arabia. The study found that relative advantages, top management support, culture, regulatory environment, owner/manager innovativeness and ICT knowledge had a significant relationship with ICT adoption among SMEs in Saudi Arabia, whereas compatibility, complexity and a competitive environment had no significant relationship with ICT adoption. The findings of this study will potentially help SME managers/owners and the Saudi government in the successful adoption and diffusion of ICT in SMEs located in rural areas in Saudi Arabia.